EFFECTIVENESS OF SUGAR DRESSING TREATMENT OF LAWANG SUGAR CANE ORIGIN ON INCISIONS WOUND HEALING OF RABBIT SKIN - Rezeki, Sri; Gunanti, Gunanti; Subangkit, Mawar (Universitas Syiah Kuala, 2024)
The aim of this research was to determine the effectiveness of sugar dressing treatment from Lawang sugar cane on incision wound healing process of rabbit skin. Nine New Zealand white rabbits were divided into three treatment groups with three rabbits per group. In negative control group (KN), the wounds were only treated with distilled water, while in SD60 and SD100 groups, the wounds were treated with 60% and 100% sugar solution, respectively. The treatment was given once daily for 7 days. The results showed that the sugar dressing treatments have significant effect (P0.05) on the size of the wound area and increased the collagen density, but did not have significant effect on the remaining length of the wound.Based on the results of the study, it can be concluded that sugar dressing dressing treatment from Lawang sugar cane is effective in increasing collagen density in the wound healing process.